Plant Genomics 2016
DOI: 10.5772/64350
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Plant Tolerance to Abiotic Stresses

Abstract: During the last 50 years, it has been shown that abiotic stresses influence plant growth and crop production greatly, and crop yields have evidently stagnated or decreased in economically important crops, where only high inputs assure high yields. The recent manifesting effects of climate change are considered to have aggravated the negative effects of abiotic stresses on plant productivity. On the other hand, the complexity of plant mechanisms controlling important traits and the limited availability of germp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 458 publications
(307 reference statements)
0
26
0
Order By: Relevance
“…Ve1 is an example of a plant receptor molecule in tomato, which binds to the Ave1 elicitor molecule from fungi. Ve1 can also be introduced as the PRR or R protein where the Ave1 peptide is referred to as the effector acting as MAMP [41][42][43].…”
Section: Plant Innate Immunity: Pre-existing Defensementioning
confidence: 99%
See 1 more Smart Citation
“…Ve1 is an example of a plant receptor molecule in tomato, which binds to the Ave1 elicitor molecule from fungi. Ve1 can also be introduced as the PRR or R protein where the Ave1 peptide is referred to as the effector acting as MAMP [41][42][43].…”
Section: Plant Innate Immunity: Pre-existing Defensementioning
confidence: 99%
“…General elicitors are involved in the general resistance signaling pathways, while race-specific elicitors are associated with R gene-mediated signaling [101]. Elicitors that are capable of triggering defense in both non-host and host plants through the perceived presence of potential pathogens are known as general elicitors [41,[102][103][104][105][106]. Most general elicitors are essentially present in pathogen cell walls as structural components e.g., glucan, chitin, flagellin, and lipopolysaccharides (LPS).…”
Section: The Elicitation Of Defense: Elicitor Molecules the Initiatomentioning
confidence: 99%
“…Their interactions with the plants evoke various kinds of local and systemic responses that improve metabolic capability of the plants to fight against abiotic stresses ( Nguyen et al, 2016 ). A testament to the important attributes of the microbial interactions with plants is significant number of accumulating pieces of evidence that suggest in-depth mechanisms based on plant–microbe interactions that offer modulation of cellular, biochemical and molecular mechanisms connected with stress tolerance ( Bakker et al, 2012 ; Onaga and Wydra, 2016 ). Growing interest in uncultured microbes, especially from the rhizosphere of the crop plants, depleted and degraded soils, soils with disturbed fertility status and endophytic communities that potentially represent ‘obligate endophytes’ inhabiting plant tissues deciphered multi-phasic functions associated with the stress tolerance in microbial communities.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Several studies reported the imperative characteristics of the microbial communications with plants that propose mechanisms based on plant-microorganism associations that accentuated the biochemical, molecular, and cellular mechanisms of plant defense against stresses. [31,32] Studies on plant microbiome at molecular, physiological, and biochemical levels observed that plant-microbes associations communicate plant responses against stress conditions. [33] Technological developments also facilitated understanding of gene editing systems, RNAi-mediated gene silencing, mutant technology, proteomic analysis, and metabolite profiling to reveal voluminous molecular information that helped in improving our understanding of microbe-interactions.…”
Section: Review Articlementioning
confidence: 99%